AVALIAÇÃO DOS EFEITOS DA CAPACITAÇÃO DE SERVIDORES EM UMA UNIVERSIDADE FEDERAL: UM ESTUDO DE CASO EM UM DEPARTAMENTO DE CONTABILIDADE E FINANÇAS - Mota, Susana Caruso (2013)
The aim of this study was to map perceptions of professional training of a Federal Public Higher Education, aimed at improving policies to qualify its servers. To achieve this goal was made to a questionnaire based on the results of literature review on competence. The predominant approach in reviewing bibiográfica analysis focused on references: competence, skills and attitude, as a set of knowledge that transform labor relations. It was also addressed, studies on the performance of perceptions in Brazil. In order to assess the perceptions of the effects of the training courses on the professional performance of its graduates, this assessment was applied to servers graduates of training courses and immediate supervisors. The original sample was developed through the case study, applied questionnaire to 30 servers in the Department of Accounting and Finance from Universidade Federal Fluminense, seven managers and twenty-three employees. The analysis of results highlights that 50-79% of respondents assessed the competence servers improving the quality of the work as having degree of high or very high importance. This same index 50-79% of managers surveyed rated competence will to empower themselves as having degree of high or very high importance. Both servers as managers demonstrated through research that both parties, there has been concern about the performance and consequently with professional competence. Thus, after analyzing the survey results, is summarized guidelines for supporting the coordination of the training courses of the institution and is expected to generate in the future unfolding of this research, inputs to assist the Dean of Personnel Management University Federal Fluminense in planning policies for the training and qualification of servers. Keywords: Competence. Personnel Management. Training.